Investigation of a Cruising Fixed Wing Mini Unmanned Aerial Vehicle Performance Optimization - Eftekhari, Shahrooz; Al-Obaidi, Abdulkareem Sh. Mahdi (Indonesian Journal of Science and Technology, 2019)
The applications of unmanned aerial vehicles have been extended through the recent decades and they are utilized for both civil and military applications. The urge to utilize unmanned aerial vehicles for civil purposes has elevated researchers and industries interest towards the mini unmanned aerial vehicle (MUAV) category due to its suitable configurations and capabilities for multidisciplinary civil purposes. This study is an effort to further enhance the aerodynamic efficiency of MUAVs through a parametric study of the wing and proposing an innovative bioinspired wing design. The research is conducted utilizing numerical simulation and experimental validation. This research provides a better understanding of different wing parameter(s) effect on the aerodynamic performance of the wing and mini unmanned aerial vehicles. A new wing configuration is designed, implemented and evaluated. The wing is named as Alpine since it is inspired by biomimicry of alpine swift bird. Evaluation of the new wing geometry shows that the Alpine wing geometry performs 35.9% more efficient compared to an existing wing with similar wing area. Hence, the aerodynamic efficiency optimization is achieved for the Alpine wing which helps to enhance the performance of MUAVs.